Study on the efficiency of cash waqf management in Malaysia - Khamis, Siti Razifah; Che Mohd Salleh, Marhanum (Bank Indonesia Institute, 2018)
The role of Waqf is synonym with the purpose of developing the economics as well as social well-being by means of a charity-based system. Revitalization of cash Waqf gives advantage to Muslims countries to further enhance this charity system. However, the efficiency of cash Waqf management is still questionable due to several internal management issues. This research is conducted to three objectives; to explore current practices of Waqf institutions in managing cash Waqf concerning human resource, documentation and reporting aspect; to investigate challenges faced by Waqf institutions in managing cash Waqf in terms of human resource, documentation and reporting aspects; and to suggest a few ways that can enhance the efficiency of cash Waqf management focusing in the three aspects. To achieve these objectives, qualitative methodology has been adopted where the data of this research was collected through semi-structured interview and review of past literatures as well as relevant documents. The finding of the research shows that majority of Waqf institutions have made efforts in promoting cash Waqf based on its regulation, financial sources, collaboration, duration of cash Waqf implementation and its strategic planning. However, the current practices of human resource, documentation and reporting are not suitable with the current pace of evolution to fully realize the benefit of cash Waqf. This research revealed the loopholes in the management of cash Waqf and suggested several ways for improvement as a reference for Waqf institutions in order to improve their cash Waqf implementation. It is a significant endeavor for Waqf institutions in Malaysia to develop knowledge on cash Waqf management as well as provoking speedy development progress of cash Waqf implementation in Malaysia.